Structure and mechanical properties of in-situ synthesized α-Ti/TiO2/TiC hybrid composites through mechanical milling and spark plasma sintering. Issue 8 (15th April 2022) - Ali, K. Showkat; Karunanithi, R.; Prashanth, M.; Sivasakaran, S.; Subramanian, B.; Jailani, H. Siddhi
Abstract: The main aim of this study was to apply high-energy longer mechanical milling and spark plasma sintering (SPS) techniques to produce in-situ α-Ti/TiO2 /TiC hybrid composites from commercially pure-Ti (CP–Ti, HCP structure) powders. The CP-Ti powders were subjected to different milling times (0, 20, 40, 60, 80, 100, and 120 h). The results showed that the powder samples milled for 120 h produced Ti, Ti3 O5, TiO, TiO2 phases, and dissolved C atoms from the process control agent (toluene) which were then converted to α-Ti, TiO2, and TiC phases (formed in-situ composites) through spark plasma sintering. This was expected due to more reactivity in the 120 h sample as longer milling introduces severe and robust structural refinements. Structural evaluations with increasing milling time were carried out using XRD, HRSEM, and HRTEM. The synthesized powders were then consolidated by SPS at pressures of 50 MPa and 1323 K for 6 min. The micro-hardness results have shown that the hardness was started to increase from 1.40 GPa to 5.56 GPa with increasing milling time due to more dislocation and pinning effect produced by grain refinement and formed TiO2 /TiC intermetallic particles enhancing the strength of α-Ti matrix. The α-Ti/TiO2 /TiC in-situ hybrid composite bulk sample yielded an ultimate compressive strength of 1.594 GPa.